Deletion of Sigmar1 leads to increased arterial stiffness and altered mitochondrial respiration resulting in vascular dysfunction - Remex, Naznin Sultana; Abdullah, Chowdhury S.; Aishwarya, Richa; Kolluru, Gopi K.; Traylor, James; Bhuiyan, Mohammad Alfrad Nobel; Kevil, Christopher G.; Orr, A. Wayne; Rom, Oren; Pattillo, Christopher B.; Bhuiyan, Md. Shenuarin (Frontiers in Physiology, 2024)
Sigmar1 is a ubiquitously expressed, multifunctional protein known for its cardioprotective roles in cardiovascular diseases. While accumulating evidence indicate a critical role of Sigmar1 in cardiac biology, its physiological function in the vasculature remains unknown. In this study, we characterized the expression of Sigmar1 in the vascular wall and assessed its physiological function in the vascular system using global Sigmar1 knockout (Sigmar1 -/-) mice. We determined the expression of Sigmar1 in the vascular tissue using immunostaining and biochemical experiments in both human and mouse blood vessels. Deletion of Sigmar1 globally in mice (Sigmar1 -/-) led to blood vessel wall reorganizations characterized by nuclei disarray of vascular smooth muscle cells, altered organizations of elastic lamina, and higher collagen fibers deposition in and around the arteries compared to wildtype littermate controls (Wt). Vascular function was assessed in mice using non-invasive time-transit method of aortic stiffness measurement and flow-mediated dilation (FMD) of the left femoral artery. Sigmar1 -/-mice showed a notable increase in arterial stiffness in the abdominal aorta and failed to increase the vessel diameter in response to reactive-hyperemia compared to Wt. This was consistent with reduced plasma and tissue nitricoxide bioavailability (NOx) and decreased phosphorylation of endothelial nitric oxide synthase (eNOS) in the aorta of Sigmar1 -/-mice. Ultrastructural analysis by transmission electron microscopy (TEM) of aorta sections showed accumulation of elongated shaped mitochondria in both vascular smooth muscle and endothelial cells of Sigmar1 -/-mice. In accordance, decreased mitochondrial respirometry parameters were found in ex-vivo aortic rings from Sigmar1 deficient mice compared to Wt controls. These data indicate a potential role of Sigmar1 in maintaining vascular homeostasis.